The two-photon production of W-bosons pair at colliders at the leading order and the one-loop correction - Manko, Andrei Yu.; Shulyakovsky, Roman G. (Journal of the Belarusian State University. Physics, 2020)
In this paper the process of two-photon production of W-bosons pair was studied at hadron and electron-positron colliders in the leading and the next-to-leading order approximation. The process can be used for investigation precision parameters of Standard Model (tri-linear and quartic couplings) and search effects of «new physics» (for example anomalous couplings). This process of production W-bosons has a small background therefore it can be studied at colliders with high precision. The program LoopTools was used to numerical calculate one-loop integrals, the program Mathematica and the packages FeynArts and FeynCalc were used to obtain the Feynman diagrams and amplitudes, the square of module of matrix element. The total and differential cross sections for hadron and electron-positron colliders were calculated using the approximation of equivalent of photons (Weizsäcker – Williams approximation). In this approximation, the scattering particles are detected in the forward-detectors at small angles and the production particles are detected in the main detector. The Monte-Carlo generator TwoPhotonGen written in C++ was used for simulation. It is shown, the total and differential cross section are increasing with increasing of the total energy of colliding particles.